2018
DOI: 10.1590/1414-431x20187566
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-coding RNAs in non-aging-related neurological disorders

Abstract: Protein coding sequences represent only 2% of the human genome. Recent advances have demonstrated that a significant portion of the genome is actively transcribed as non-coding RNA molecules. These non-coding RNAs are emerging as key players in the regulation of biological processes, and act as "fine-tuners" of gene expression. Neurological disorders are caused by a wide range of genetic mutations, epigenetic and environmental factors, and the exact pathophysiology of many of these conditions is still unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
0
11
0
1
Order By: Relevance
“…cfRNAs can be classified as protein-coding (mRNAs) or non-coding RNAs. Non-coding RNAs are further classified according to size as small non-coding RNAs (sncRNAs), including microRNAs and lncRNAs ( 35 , 36 ). The most recent studies that investigated the application of cfRNAs as biomarkers in plasma and serum have focused on non-coding RNAs, especially microRNAs ( 35 ).…”
Section: Circulating Cfrnamentioning
confidence: 99%
See 3 more Smart Citations
“…cfRNAs can be classified as protein-coding (mRNAs) or non-coding RNAs. Non-coding RNAs are further classified according to size as small non-coding RNAs (sncRNAs), including microRNAs and lncRNAs ( 35 , 36 ). The most recent studies that investigated the application of cfRNAs as biomarkers in plasma and serum have focused on non-coding RNAs, especially microRNAs ( 35 ).…”
Section: Circulating Cfrnamentioning
confidence: 99%
“…An interesting aspect of microRNA-mediated gene regulation is its complexity: a single microRNA can regulate many mRNAs, and one mRNA can be regulated by multiple microRNAs ( 39 ). Although RNA molecules are relatively unstable and susceptible to degradation by Rnases – a protein superfamily generally abundant in biofluids ( 10 ) – studies have shown that microRNAs are particularly stable and resistant to nuclease digestion in the plasma and serum ( 24 , 35 , 36 ). Thus, microRNAs represent an easily assayed molecule.…”
Section: Circulating Cfrnamentioning
confidence: 99%
See 2 more Smart Citations
“…Non-coding RNAs (ncRNAs), including microRNAs and long non-coding RNAs (lncRNAs), contribute to diverse biological processes by regulating the expression of mRNA targets at the post-transcriptional level (Bali and Kuner, 2014; Zhou et al, 2017) by targeting several pain pathways (Tan et al, 2015; Plassais et al, 2016; Shao et al, 2018). Dysregulation of non-coding RNAs has also been implicated in the development of neuropathic pain (Liu et al, 2017; Vieira et al, 2018). For example, lncRNA BC168687 is associated with diabetic neuropathic pain (Liu et al, 2018), while lncRNA MRAK009713, NEAT1, and XIST can regulate chronic constriction injury-induced neuropathic pain (Li et al, 2017; Xia et al, 2018; Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%